Religião e poder : uma crítica da teologia cristã - Souza Júnior, José Sebastião de (2014)
This work is a study about power strategies used throughout the history of the Judaic-Christian religion in a socio-political, critic-historical, theological vision, from the Biblical tribalism period, to the capitalistic period, the nowadays reality, in which one perceives the necessity of a religion committed to the poor. It can be observed that the public dimension of religious life has been restricted to individual beliefs, personal rituals and private activities, focused on each person s gains and benefits. As such Christianity has personal characteristics. Viewing from this context, obviously secular, we examine how religion should position itself and what activities it should assume that would favor those on the margin of society .The proposal is to know which power strategies were used historically by the Judaic-Christian religion, with the intention of remaining in power, and identify historically the opportune way to maintain the oppressor in power; present through Theology of Liberation ( Teologia da Libertação), the commitment this religion should alongside the poor and all other persons.